Perspectives of pain specialists, patients, and family members on long-term opioid use for chronic non-cancer pain: a qualitative study - Rattaphol Seangrung (BMC, 2021)
Abstract Background Opioids are currently prescribed for chronic non-cancer pain (CNCP), and some patients use opioids continuously for long-term treatment. Stakeholders’ awareness about long-term opioid therapy is essential for improving the safety and effectiveness of pain treatment. The purpose of this study is to explore the perspectives of pain specialists, patients, and family caregivers about long-term opioid use in CNCP management. Methods This study was a qualitative study and adhered to the COREQ guidelines. Pain specialists (n = 12), patients (n = 14), and family members (n = 9) were recruited to the study by purposive sampling at the Pain Clinic of Ramathibodi Hospital. Semi-structured interviews were recorded, verbatim transcribed, conceptually coded, and analyzed using Atlas.ti 8.0. Results All groups of participants described opioids as non-first-line drugs for pain management. Opioids should be prescribed only for severe pain, when non-opioid pharmacotherapy and non-pharmacological therapies are not effective. Patients reported that the benefits of opioids were for pain relief, while physicians and most family members highlighted that opioid use should improve functional outcomes. Physicians and family members expressed concerns about opioid-related side effects, harm, and adverse events, while patients did not. Patients confirmed that they would continue using opioids for pain management under supervision. However, physicians stated that they would taper off or discontinue opioid therapy if patients’ pain relief or functional improvement was not achieved. Both patients and family members were willing to consider non-pharmacological therapies if potential benefits existed. Patient education, doctor–patient/family relationships, and opioid prescription policies were proposed to enhance CNCP management. Conclusion Long-term opioid therapy for CNCP may be beneficial in patients who have established realistic treatment goals (for both pain relief and functional improvement) with their physicians. Regular monitoring and evaluation of the risks and benefits, adverse events, and drug-related aberrant behaviors are necessary. Integrated multimodal multidisciplinary therapies and family member collaborations are also important for improving CNCP management.